433 Talimogene laherparepvec (T-VEC) in combination with ipilimumab (IPI) versus IPI alone for advanced melanoma: 4-year interim analysis of a randomized, open-label, phase 2 trial. (10th December 2020) - Puzanov, Igor; Chesney, Jason; Collichio, Frances; Singh, Parminder; Milhem, Mohammed; Glaspy, John; Hamid, Omid; Ross, Merrick; Friedlander, Philip; Garbe, Claus; Logan, Theodore; Hauschild, Axel; et al.
Abstract : Background: This is the first randomized trial evaluating an oncolytic virus with an immune checkpoint inhibitor in advanced melanoma. Improved objective response rate (ORR) was observed for T-VEC plus IPI compared to IPI alone (39% vs. 18%; OR 2.9; 95% Cl, 1.5–5.5; P=0.002). 1 At 3-year follow-up, median OS was not reached in either arm (HR, 0.85; 95% CI, 0.55–1.32; P=0.480). 2 Here we present 4-year interim analysis results including BRAF V600 mutation subgroup analysis. Methods: Patients with unresectable or metastatic (IIIB-IV) melanoma were randomized 1:1 to receive T-VEC plus IPI or IPI alone. T-VEC was injected day 1, week 1, at 106 PFU/mL, followed by 108 PFU/mL on day 1, week 4, and Q2W thereafter. IPI (3 mg/kg) was given Q3W starting day 1, week 6, up to 4 doses, for T-VEC arm; day 1, week 1 for IPI alone. Response was assessed per immune-related response criteria (irRC) Q12W until disease progression. The primary endpoint was ORR; key secondary endpoints were overall survival (OS), progression-free survival (PFS), durable response rate (DRR), and safety (NCT01740297 ). Results: A total of 198 patients (98 combination, 100 IPI alone) were randomized. As of February 25, 2020, median follow-up was 48.3 months for combination and 35.7 months for IPI alone. DRR improved for combination vs. IPI (33.7% vs. 13.0%; OR 3.4; 95% CI, 1.7–7.0; P=0.001). Median PFS was 13.5 months with combination and 6.4 months with IPI (HR 0.81; 95% Cl, 0.57–1.15; P=0.23). Median OS was not reached for combination and was 50.1 months for IPI (HR 0.82; 95% CI, 0.54–1.25; P=0.36). For combination, 47 (48.0%) patients received subsequent anti-cancer therapy vs. 64 (64.0%) for IPI; median time from randomization to first subsequent therapy was 27.7 months and 8.3 months, respectively. In subgroup analysis, patients without BRAF V600 mutation (63% combination, 60% IPI) improved DRR and PFS for combination vs. IPI alone (DRR: 33.9% vs. 5.0%; median PFS: 18.0 months vs. 4.5 months); BRAF V600 mutation positive patients (36% combination, 34% IPI) were similar between arms (DRR: 34.3% vs. 26.5%; median PFS: 4.2 months vs. 6.4 months). No additional safety signals observed in follow-up. Conclusions: The improved PFS and DRR for the combination arm at 4-year follow-up indicates continued benefit of combination therapy. Patients receiving IPI alone were more likely to receive subsequent anti-cancer therapy in a shorter time. Subsequent anticancer therapies may confound OS analysis. The BRAF mutant post-hoc analysis requires further mechanistic investigation. Acknowledgements: The authors thank the investigators, patients, and study staff who contributed to this study. The study was sponsored and funded by Amgen Inc. Medical writing support was provided by Christopher Nosala (Amgen Inc.). Trial Registration: NCT01740297 Ethics Approval: The study was approved by all institutional ethics boards. References: Chesney J, Puzanov I, Collichio F, et al. Randomized, open-label phase II study evaluating the efficacy and safety of talimogene laherparepvec in combination with ipilimumab versus ipilimumab alone in patients with advanced, unresectable melanoma. J Clin Oncol 2018;36 :1658–1667. Chesney JA, Puzanov I, Collichio F, et al. Talimogene laherparepvec (T-VEC) in combination (combo) with ipilimumab (ipi) versus ipi alone for advanced melanoma: 3-year landmark analysis of a randomized, open-label, phase 2 trial. Ann Oncol 2019;30:mdz394-067.